Answer:
solution is (- 3, 5 )
Step-by-step explanation:
given the 2 equations
6x - y = - 23 → (1)
8x + 3y = - 9 → (2)
rearrange (1) expressing y in terms of x
y = 6x + 23 → (3)
Substitute y = 6x + 23 into (2)
8x + 3(6x + 23 ) = - 9
8x + 18x + 69 = - 9
26x + 69 = - 9 ( subtract 69 from both sides )
26x = - 78 ( divide both sides by 26 )
x = - 3
substitute x = - 3 into (3)
y = (6 × - 3 ) + 23 = - 18 + 23 = 5
solution is (- 3, 5 )
Answer:
what r they teaching u guys at yo school
Step-by-step explanation:
anyway u use a rule to figure this out look up rule math and it will help u
Answer:
4/25
Step-by-step explanation:
12 divided by 3
72 divided by 3
Greatest Common Divisor:
3
So 12/72 simplifed would be 4/25 and the GCD would be 3.
Answer:
if u multiply 20 times 5 u would get 100 and and if u add 20+20+20+20+20 u would get 100 so either way ur answer may be 5
Answer:
1. m = 45
2. x = -18
3. x = -13
4. x = 11
5. x = 19
6. v = 3
7. n = 208
8. b = -1
Step-by-step explanation: